Perlindungan Anak dari Ancaman Child Grooming di Indonesia: Evaluasi Regulasi dan Rekomendasi Pembaruan Hukum dalam Era Digital (SETARA : Jurnal Ilmu Hukum, 2024)
The phenomenon of child grooming has become a major challenge in child protection in the digital era. This practice involves manipulative efforts by adults to approach children, build emotional relationships, and exploit them sexually, either directly or through electronic media. In Indonesia, although regulations such as the Child Protection Law and the Information and Electronic Transactions Law can be used to respond to this problem, legal gaps remain, especially for conduct occurring in cyberspace. Using a qualitative approach with library research, this study examines child grooming from the perspective of Indonesian law, analyses weaknesses in the existing legal framework, and offers recommendations for legal reform. The study finds that Indonesia already has a basic legal framework to address this conduct, but the current regulations have not yet been fully effective in dealing with acts committed through social media and digital platforms. Therefore, regulatory reform and stronger law-enforcement capacity are needed to protect children from grooming threats.